Voluntary disclosure and relational connectivity: The case of the Polish bond market - Dominika Hadro; Marek Pauka; Kamil Gemra; Szymon Okoń; Justyna Fijałkowska (Journal of Banking and Financial Economics (JBFE), 2022)
The purpose of our research is to evaluate the voluntary disclosure strategy and effective communication between issuers and investors on the Polish bond market Catalyst. We conducted a questionnaire among issuers on the Catalyst. To evaluate the data and find answers to the research questions, we used the Qualitative Comparative Analysis. As our analysis shows that management board engagement seems crucial for effective communication, we claim that in relatively smaller capital markets, personal engagement of board members in preparing voluntary disclosure should be considered a proxy of a high disclosure strategy quality. We prove that companies use dialogue with investors in private rather than in public to understand their communication expectations. This finding indicates the essential limitations of previous research evaluating relational connectivity through social media. We point out the existence of many paths to achieve a high level of companies' perception of investors' voluntary disclosure needs and companies' relational connectivity regarding voluntary disclosure. We developed a new approach to measuring relational connectivity, which can be successfully applied to other markets and stock exchanges, allowing verification of previous findings and the development of a new approach to conducting research. We claim that it is necessary to put more pressure on the management board's engagement in preparing the financial report as it is crucial for understanding investors' voluntary disclosure needs. Our conclusions question the growing societal pressure on engaging in activity in social media as a key concept of effective communication.
Keywords: G14; G23; D82; 330; voluntary disclosure; relational connectivity; bond market; Poland; corporate communication